High-toughness concrete material prepared by synthesizing hydrated calcium carboaluminate fiber from cementing material and preparation method of high-toughness concrete material

By using waste such as hydrated calcium carbonate aluminate fiber and gold tailings sand in high-tough concrete, the problems of high cost and environmental pollution of existing high-tough concrete materials are solved, and the improvement of material performance and resource recycling are achieved.

CN119841584APending Publication Date: 2025-04-18HOHAI UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510017990.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

While improving performance, existing high-tough concrete materials use expensive PVA fibers and a large number of chemical additives, resulting in high costs and environmental pollution, limiting their wide range of applications.

Method used

By synthesizing hydrated calcium carbonate fibers by gelling materials, combining waste such as gold tailings sand, a new high-tough concrete material is prepared, which reduces resource waste and environmental pollution, and significantly improves the strength and toughness of concrete.

Benefits of technology

This method not only reduces material costs and simplifies the preparation process, but also achieves the dual goals of resource recycling and environmental protection, so that concrete has a higher ability to adapt to complex engineering needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a high-toughness concrete material prepared from hydrated calcium carbonate aluminate fibers synthesized from a cementing material and a preparation method of the high-toughness concrete material, and belongs to the technical field of concrete materials. The concrete material is prepared from the following raw materials in parts by weight: 100 to 500 parts of hydrated calcium aluminate fibers, 200 to 400 parts of gold tailing sand, 200 to 400 parts of cement, 300 to 900 parts of fly ash, 2 to 10 parts of a water reducing agent, 1000 to 3000 parts of water and 10 to 30 parts of PE fibers. According to the hydrated calcium carbonate aluminate fiber prepared by the method, resource waste and environmental pollution are reduced; and the hydrated calcium carboaluminate fiber synthesized by the method obviously improves the strength and toughness of the concrete, so that the concrete can better adapt to complex engineering requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete materials, and in particular to a high-toughness concrete material synthesizing hydrated calcium aluminate carbon fibers from a cementitious material and a preparation method thereof. Background Art

[0002] In modern buildings and infrastructure construction, concrete is a widely used building material, and its continuous improvement in performance is of vital importance to engineering quality and safety. With the increasing complexity of engineering structures and the diversification of use environments, higher and higher requirements are placed on the high toughness of concrete. High-strength concrete can withstand greater loads, reduce the size and weight of the structure, and thus save materials and space. High-toughness concrete can effectively resist the expansion of cracks, improve the durability and seismic resistance of the structure, and extend the service life of the building.

[0003] In order to achieve the high toughness of concrete, fiber materials are usually added to concrete. Among them, PE fiber, as a common man-made fiber, plays a certain role in improving the performance of concrete. However, the production cost of PE fiber is relatively high, which undoubtedly increases the overall cost of concrete.

[0004] On the other hand, in industrial activities such as gold mining, a large amount of waste such as tailings sand is generated. The accumulation of these wastes not only occupies precious land resources, but also may cause serious pollution and ecological damage to the surrounding environment. If these wastes can be used reasonably, it can not only reduce environmental pressure, but also provide new ideas for the development of concrete materials.

[0005] The Chinese patent application number CN202110519358 discloses a high-toughness concrete and its preparation method; its raw materials, by weight, include 150-170 parts of water, 200-250 parts of cement, 200-250 parts of coarse aggregate, 350-400 parts of fine aggregate, 40-70 parts of ultrafine powder, 50-70 parts of structural modification material, 10-20 parts of cellulose and 10-25 parts of chemical additives; its preparation method is: weigh cement, coarse aggregate, fine aggregate, ultrafine powder, structural modification material, cellulose, chemical additives according to the formula amount and mix them evenly; add water to the mixture according to the formula ratio, stir to obtain high-toughness concrete slurry. The concrete of this application has high strength and toughness, and can be used in some construction occasions with greater pressure. Its preparation method has the advantages of simple proportioning, easy construction, and easy availability of raw materials. However, a large amount of chemical additives are used, including hydroxypropyl methylcellulose, hydroxyethyl cellulose, epoxy-modified phenolic resin and coupling agent, which increases the use cost of high-toughness concrete; the material preparation process requires N2 protection, which is difficult to produce, costly and has a long cycle, limiting the large-scale application of high-toughness concrete; the use of relatively expensive PVA fiber limits the scope of use of high-toughness concrete. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a high-toughness concrete material and a preparation method thereof by synthesizing hydrated calcium aluminate fibers from cementitious materials. The prepared hydrated calcium aluminate fibers reduce resource waste and environmental pollution; and the hydrated calcium aluminate fibers synthesized by this method significantly improve the strength and toughness of concrete, enabling it to better adapt to complex engineering requirements.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, the present invention provides a high-toughness concrete material synthesized from a cementitious material and calcium aluminate hydrate fiber, which is prepared from the following parts by weight:

[0009] 100-500 parts of hydrated calcium aluminate carbon fiber, 200-400 parts of gold tailings sand, 200-400 parts of cement, 300-900 parts of fly ash, 2-10 parts of water reducer, 1000-3000 parts of water, and 10-30 parts of PE fiber.

[0010] Preferably, the steel slag, metakaolin, gold tailings and water are mixed, carbon dioxide is introduced, and the mixture is stirred for reaction, and then the carbonized solid mixture is centrifuged and dried to obtain hydrated calcium aluminate carbonate fibers;

[0011] The mass ratio of steel slag, metakaolin and gold tailings sand is 1:1:1:(10-20);

[0012] The specific surface area of ​​the steel slag is 400-430m2 / kg, calcium oxide content is higher than 35%.

[0013] The carbon dioxide ventilation volume is 0.1-0.3 L / min / 100 mL.

[0014] Preferably, the whiteness of the metakaolin should be ≥85%, and the aluminum oxide content should be 38%-45%, wherein particles with a particle size of less than 2 μm account for no less than 80%.

[0015] Preferably, the fineness modulus of the gold tailings sand is 2.0-3.0, and the mud content is less than 5%.

[0016] Preferably, the strength grade of the cement is not less than 42.5.

[0017] Preferably, the fly ash has a fineness of ≤20%, a water requirement ratio of ≤105%, and a loss on ignition of ≤8%.

[0018] Preferably, the water reducing agent has a water reducing rate of ≥20%.

[0019] In a second aspect, the method for preparing the high-toughness concrete material of the present invention comprises the following steps:

[0020] (1) weighing the raw materials according to the weight parts;

[0021] The mass ratio of steel slag, metakaolin and gold tailings sand is 1:1:1:(10-20);

[0022] (2) Cement, fly ash and water reducing agent are mixed evenly, and then the remaining water is added and stirred evenly. Then hydrated calcium aluminate carbon fiber and the remaining gold tailings sand are added and stirred evenly. Then PE fiber is added and stirred evenly. The mixture is poured into shape and cured to obtain a high-toughness concrete material.

[0023] Preferably, the stirring speed in step (2) is 100-300 r / min.

[0024] Preferably, in step (2), the curing temperature is 95%±2% and the temperature is 20°C±2°C in a curing room for 28 days.

[0025] The preparation principle of hydrated calcium aluminate carbon fiber is:

[0026] When steel slag, metakaolin, and gold tailings are placed in water and carbon dioxide is introduced, a series of reactions will occur. First, the calcium oxide in the steel slag reacts with carbon dioxide to form calcium carbonate. The reaction equation is as follows:

[0027] CaO+CO2→CaCO3

[0028] The carbonization rate of steel slag itself is not high, but its reaction degree will be greatly increased in aqueous solution. At the same time, due to the presence of gold tailings, gold tailings can act as crystal nuclei to reduce the reaction barrier of steel slag carbonization, thereby increasing the carbonization reaction degree of steel slag. Metakaolin will generate aluminum phase ions when dissolved in water. The calcium carbonate generated by carbonization of steel slag will react with aluminum to generate water and calcium aluminate fiber. The reaction equation is as follows:

[0029] 3CaO·Al2O3+CaCO3+11H2O→3CaO·Al2O3·CaCO3·11H2O. By adopting the above technical solution, the present invention obtains hydrated calcium aluminate carbon fiber through an innovative preparation method, which has unique physical and chemical properties. Compared with traditional PE fiber, it has significant advantages in improving concrete performance, and the cost is relatively low, while achieving the dual goals of resource recycling and environmental protection.

[0030] The needle-shaped hydrated calcium aluminate carbon fibers generated by the present invention are evenly distributed in the concrete, which can effectively prevent the expansion of cracks. When the concrete is subjected to external force, the fibers can bear part of the tension, thereby improving the tensile strength and toughness of the concrete.

[0031] Contains at least the following beneficial technical effects:

[0032] (1) The hydrated calcium aluminate carbonate fibers prepared by the present invention reduce resource waste and environmental pollution; moreover, the hydrated calcium aluminate carbonate fibers synthesized by the method significantly improve the strength and toughness of concrete, enabling it to better adapt to complex engineering requirements.

[0033] (2) Compared with traditional concrete using PE fibers, the present invention has obvious cost advantages, which is beneficial to reducing project costs. In addition, the entire preparation process is relatively simple and utilizes carbon dioxide, which can reduce carbon emissions. It is easy to promote and apply in actual production and has good industrialization prospects. DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] The "room temperature" and "normal temperature" mentioned in the present invention are all calculated as 25±2°C unless otherwise specified.

[0040] The raw materials and instruments used in the following examples of the present invention are commercially available unless otherwise specified.

[0041] Example 1

[0042] A method for preparing a high-toughness concrete material by synthesizing hydrated calcium aluminate carbon fibers from a cementitious material:

[0043] (1) Preparation of hydrated calcium aluminate carbon fiber: Steel slag, metakaolin, and gold tailings were placed in water at a mass ratio of 1:1:1 (solid-liquid ratio of 50 g / L) and carbon dioxide was introduced (gas flow rate 0.1 L / min / 100 mL). The mixture was stirred (stirring speed 500 r / min). After the reaction lasted for 2 h, the solution was centrifuged, the carbonized solid mixture was taken out, and dried for later use.

[0044] (2) Weighing raw materials by weight;

[0045] (3) 300 parts of cement and 900 parts of fly ash were placed in a mixer and stirred at a low speed (100 rpm) for 2 minutes. Then, 420 parts of water and 4 parts of water reducing agent were added and stirred at a high speed (200 rpm) for about two minutes. Then, 320 parts of gold tailings and 110 parts of the carbonized solid mixture prepared in the above steps were added and stirred at a low speed (100 rpm) for 2 minutes. Then, 18 parts of PE fiber were added and stirred at a high speed (200 rpm) for five minutes. Finally, the mixture was molded and cured at room temperature for 24 days before demolding. Then, the mixture was placed in a curing room at a temperature of 95%±2% and a temperature of 20°C±2°C for 28 days.

[0046] Embodiment 2:

[0047] The preparation steps of this embodiment are the same as those of Example 1, except that the carbon dioxide ventilation rate in step (1) is 0.2 L / min / 100 mL.

[0048] Embodiment 3:

[0049] The preparation steps of this embodiment are the same as those of Example 1, except that the carbon dioxide ventilation rate in step (1) is 0.3 L / min / 100 mL.

[0050] Example 4

[0051] The preparation steps of this embodiment are the same as those of Embodiment 3, except that in step (3), 300 parts of cement and 900 parts of fly ash are put into a mixer and stirred at a low speed (100 rpm) for 2 minutes, then 420 parts of water and 4 parts of water reducing agent are added and stirred at a high speed (200 rpm) for about two minutes, then 215 parts of gold tailings and 215 parts of carbonized solid mixture are added and stirred at a low speed (100 rpm) for 2 minutes, then 12 parts of PE fiber are added and stirred at a high speed (200 rpm) for five minutes, finally, molded, cured at room temperature for 24 hours, and then demolded, and then placed in a curing room under the conditions of a temperature of 95%±2% and a temperature of 20°C±2°C for curing for 28 days.

[0052] Example 5

[0053] The preparation steps of this embodiment are the same as those of embodiment 3, except that in step (3), 300 parts of cement and 900 parts of fly ash are put into a mixer and stirred at a low speed (100 rpm) for 2 minutes, then 420 parts of water and 4 parts of water reducing agent are added and stirred at a high speed (200 rpm) for about two minutes, then 110 parts of gold tailings and 320 parts of carbonized solid mixture are added and stirred at a low speed (100 rpm) for 2 minutes, then 6 parts of PE fiber are added and stirred at a high speed (200 rpm) for five minutes, finally molded and cured at room temperature for 24 seconds before demolding, and then placed in a curing room at a temperature of 95%±2% and a temperature of 20°C±2°C for curing for 28 days.

[0054] Example 6

[0055] The preparation steps of this embodiment are the same as those of embodiment 3, except that in step (3), 300 parts of cement and 900 parts of fly ash are put into a mixer and stirred at a low speed (100 rpm) for 2 minutes, then 420 parts of water and 4 parts of water reducing agent are added and stirred at a high speed (200 rpm) for about two minutes, then 430 parts of the carbonized solid mixture are added and stirred at a low speed (100 rpm) for 2 minutes, then stirred at a high speed (200 rpm) for five minutes, finally molded and cured at room temperature for 24 seconds before demolding, and then placed in a curing room at a temperature of 95%±2% and a temperature of 20°C±2°C for curing for 28 days.

[0056] Comparative Example 1

[0057] Put 300 parts of cement and 900 parts of fly ash into a mixer and stir at low speed (100 rpm) for 2 minutes. Then add 420 parts of water and 4 parts of water reducer and stir at high speed (200 rpm) for about two minutes. Then add 430 parts of gold tailings and stir at low speed (100 rpm) for 2 minutes. Then add 25 parts of PE fiber and stir at high speed (200 rpm) for five minutes. Finally, pour the mold and solidify it at room temperature for 24 days before removing the mold. Then put it into a curing room at a temperature of 95%±2% and a temperature of 20℃±2℃ for curing for 28 days.

[0058] According to the specification "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB / T 50081-2019, the performance of the materials prepared in the above examples was tested, including indicators such as compressive strength, tensile strength and tensile strain, and the aspect ratio of the fiber was tested. The results are shown in Table 1:

[0059] Table 1 Performance test table

[0060]

[0061]

[0062] By comparing Example 1 with other examples, it can be seen that the compressive strength, tensile strength and tensile strain of the concrete prepared by using the hydrated calcium aluminate carbonate mixture instead of the PE fiber are comparable to those of the concrete without adding the hydrated calcium aluminate carbonate mixture.

[0063] By comparing Examples 1, 2, and 3, it can be seen that increasing the flow rate of carbon dioxide will increase the aspect ratio of hydrated calcium aluminate, and the increase in aspect ratio will promote the improvement of tensile strength and tensile strain, but the growth of Example 4 relative to Example 3 is not very significant, so the carbon dioxide flow rate can be taken as an intermediate value of 0.2L / min / 100mL, and the increase in aspect ratio has no obvious effect on compressive strength.

[0064] By comparing Examples 1, 4, 5, and 6, it can be seen that as the substitution rate of hydrated calcium aluminate carbonate increases, the tensile strength and tensile strain first increase and then decrease, and the effect on the compressive strength is not obvious. The tensile strength and tensile strain of the concrete prepared in Example 4 are the highest.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-toughness concrete material synthesized from cementitious materials and calcium aluminate hydrate fibers, characterized in that: It is prepared from the following parts by weight: 100-500 parts of hydrated calcium aluminate carbon fiber, 200-400 parts of gold tailings sand, 200-400 parts of cement, 300-900 parts of fly ash, 2-10 parts of water reducer, 1000-3000 parts of water, and 10-30 parts of PE fiber.

2. The high-toughness concrete material according to claim 1, characterized in that: The preparation method of the hydrated calcium aluminate carbonate fiber is as follows: steel slag, metakaolin, gold tailings sand and water are mixed, carbon dioxide is introduced, and the mixture is stirred for reaction, and then the carbonized solid mixture is centrifuged and dried to obtain the hydrated calcium aluminate carbonate fiber; The mass ratio of steel slag, metakaolin and gold tailings sand is 1:1:1:(10-20); The specific surface area of ​​steel slag is 400-430m 2 / kg, calcium oxide content is higher than 35%.

3. The preparation method according to claim 2, characterized in that: The carbon dioxide ventilation volume is 0.1-0.3 L / min / 100 mL.

4. The high-toughness concrete material according to claim 1, characterized in that: The whiteness of the metakaolin should be ≥85%, and the aluminum oxide content should be 38%-45%; the particles with a particle size of less than 2 μm account for no less than 80%.

5. The high-toughness concrete material according to claim 1, characterized in that: The fineness modulus of the gold tailings sand is 2.0-3.0, and the mud content is less than 5%.

6. The high-toughness concrete material according to claim 1, characterized in that: The strength grade of the cement is not less than 42.

5.

7. The high-toughness concrete material according to claim 1, characterized in that: The fly ash has a fineness of ≤20%, a water requirement ratio of ≤105%, and a loss on ignition of ≤8%.

8. The high-toughness concrete material according to claim 1, characterized in that: The water reducing agent has a water reducing rate of ≥20%.

9. The method for preparing the high-toughness concrete material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) weighing the raw materials according to the weight parts; (2) Cement, fly ash and water reducing agent are mixed evenly, and then the remaining water is added and stirred evenly. Then hydrated calcium aluminate carbon fiber and the remaining gold tailings sand are added and stirred evenly. Then PE fiber is added and stirred evenly. The mixture is poured into shape and cured to obtain a high-toughness concrete material.

10. The preparation method according to claim 9, characterized in that: The stirring speed in step (2) is 100-300 r / min.

Citation Information

Patent Citations

  • High-strength and high-toughness concrete and preparation method thereof

    CN113264728A